An Overture for eCAM: Science, Technology and Innovation Initiation for Prosperous, Healthy Nepal. (5th June 2011) - Kaphle, Krishna; Bhuju, Dinesh Raj; Jha, Pramod Kr; Bhattarai, Hom Nath
Abstract : Nepal the "Shangri-La" in the lap of the Himalayas is gearing up for modern times as it starts rebuilding after a decade of senseless violence and destruction. The nation one of the poorest in the global development index is rich in natural resources and biodiversity. Reports of medicinal plants far exceeding those recorded and reported so far are encouraging and at the same time concerns for medicinal plants under threat as a result of overexploitation are emerging from Nepal. The harsh mountain terrains, lack of industrialization and harnessing potentiality of its areas of strength; water; natural resources and tourism make it poor in per capita income which averages ~ 300 US$, with half the population living under >1$ a day. Nepal is beginning to realize that the way ahead is only possible through the path of Science and Technology (ST). Nepal Academy of Science and Technology formerly known as Royal Academy of Science and Technology organized the fifth national conference held every 4 years that took place in the capital Kathmandu during November 10-12, 2008. The ST initiation event saw the participation of ~ 1400 people representing over 150 organizations from the country and experts from abroad. The theme for the fifth national meet was "Science, Technology and Innovation for Prosperous Nepal". Complementary and Alternative Medicine (CAM) was an important theme in the event as the realization for the need of ST research focused in CAM for harnessing the chemo diversity potential was univocally approved.